PENGEMBANGAN MEDIA MODUL BIMBINGAN DAN KONSELING UNTUK MEREDUKSI PROKRASTINASI AKADEMIK PADA PESERTA DIDIK KELAS VIII DI SMP AN-NAJA BOARDING SCHOOL - Susilawati, Aas; Sobari, Teti; Novianti, Williya (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study aims to develop a product in the form of a guidance and counseling module service media to reduce academic procrastination in students. This study uses the RnD (Research and Development) method. The subjects in this study were students of class VIII at SMP An-Naja Boarding School, totaling 25 people. The product validity test was carried out by material experts, media experts, practitioners and students' responses to the module media products. The results showed that the development of the guidance and counseling module media to reduce academic procrastination obtained an average result of 96.5% indicating the feasibility of a product with a very suitable category so that it could be used in the implementation of classical guidance services.